NASIONALISME PEREMPUAN D(AR)I JAWA KAJIAN BUDAYA ATAS NOVEL DURGA UMAYI Y.B. MANGUNWIJAYA - A. Windarto (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
The 1945-1949 Indonesian Revolution was a historic time and place, especially for those who witnessed and experienced such a terrible event. Through his novel entitled Durga Umayi (1991), Y.B. Mangunwijaya or Father Mangun, were able to narrate the steps of the nationalist women. Although committed "not a man", but the fictional character "Iin", "Tiwi", or whatever his name is, can show that the Indonesian Revolution that began with the Proclamation of Independence 17-81945 is very controversial. With structural and semantic studies from A.J. Greimas, it became apparent that the nationalism of women from Java was filled with imaginations that might not have been imagined at all.  Keywords: Durga Umayi, Revolution 1945-1949, Iin/Tiwi